Gendered right(s): moral and legal crossroads to think about motherhood in prison - Garibaldi Revoir, Cecilia (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2019)
In this article, I propose to think on/upon the tensions between the different levels of discussion and reflection on the phenomenon of maternity in jail which involves emotional, legal and moral issues from an ethnographic research I did in mother’s prison with children in Montevideo, Uruguay in 2017. How does the legal regulations dialogue with the moralities surrounding the right of mothers to live with their children in jail? How are these tensions reflected in the practices and speeches of both prisoners and prison officials? What are the effects of these tensions on the ways of exercising motherhood? These are some of the questions that I intend to answer in a dialogue between law, morals and gender.